Changes of sand density impact on water filter backwashing - Dąbrowski , Wojciech; Plata , Monika (Instal, 2020)
Media of rapid filters is the subject of abrasion and coverage by biofilm which partially is not removed during backwashing. The empirical tests done for predicting the optimal backwash intensity as a function of water temperature proved that in computing the sand expansion it is necessary to take into consideration not only changes of the grains’ shape but also the density of sand grains as the result of growing biofilm.
Keywords: filter backwashing; sand; biofilm; backwash intensity